Practice of advanced integrated education at the course for registered dietitians - Shimada, Mikiko; Saito, Yoko; Masuno, Yayoi; Tachibana, Yohko; Kanbe, Mieko; Miyahara, Kimiko (BULLETIN OF KIRYU UNIVERSITY, 2020)
In“ Registered dietitian comprehensive exercise II”, which is a compulsory subject in the 4th year of the department of nutrition,Kiryu University, we educated the knowledge and skills of specialized practical subjects based on the knowledge acquiredin the basic subjects, and nutrition education ability, management ability and communication ability to improve the comprehensiveapplication skills in remote teaching system.　Through all 15 lessons, we organized the lessons with learning contents thatcan developly integrate the ability, and by incorporating exercises based on group work, the students accepted various ideasand derived the optimum method.　Due to this, they acquired the applied ability to integrate the knowledge and technology requiredof advanced registered dietitians who will lead the 21st century and connect theory and practice, and the practical abilityto discover problems by yourself and solve problems in collaboration with multiple occupations.　In the future, it is necessaryto establish this exercise as a subject that will lead to the development of registered dietitians who can contribute to the localcommunity, while making improvements with a view to professional ethics and research ability.